PERANAN PENGURUS DIVISI HIV YAYASAN MEDAN PLUS DALAM MENGHAPUS STIGMA DAN DISKRIMINASI TERHADAP ORANG DENGAN HIV/AIDS (ODHA) - Sianipar, Roida Mariati (Jurnal Analisis Pendidikan Sosial, 2024)
Stigma and discrimination against people living with HIV/AIDS (PLWHA) is a substantial challenge in the prevention and control of HIV/AIDS. This stigma perpetuates myths and results in discriminatory treatment, hindering care, support, and treatment of PLWHA, leading to negative physical, psychological and social consequences. The management of the Medan Plus Foundation HIV Division is working diligently to eliminate PLWHA stigma and discrimination. This study centres on the management's role in attaining the objective. Descriptive research methods using a qualitative approach are employed in the research methodology, incorporating observation, documentation, and purposively chosen informant interviews for primary data collection. The use of secondary data collection techniques supports the primary data and achievement of research objectives. The study shows that the HIV Division Management of the Medan Plus Foundation plays a crucial role in fighting stigma and discrimination against people living with HIV/AIDS (PLWHA). This is achieved through outreach, support, the establishment and enhancement of peer support groups, network development, socialisation, and advocacy.